2018
DOI: 10.1371/journal.pone.0200304
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different revision procedures for infected megaprostheses in musculoskeletal tumour surgery of the lower limb

Abstract: PurposeThe incidence of recurrent infections in patients following one or two stage revision for infected megaprostheses after resection of bone tumours was investigated. The difference between retaining at least one well fixed stem and a complete removal of the megaprosthesis during a two stage revision was also analysed.Methods627 patients who experienced a replacement of a musculoskeletal tumour by megaprostheses were recorded. An infection occurred in 83 of 621 patients available for follow-up. 61 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
1
34
0
6
Order By: Relevance
“…Periprosthetic infection is a major postoperative complication of prosthesis. Tumor prosthesis has been shown to have a much higher postoperative infection rate (8%–15%) [ 10 , 19 , 21 ] compared with routine total joint replacements such as total hip arthroplasty and total knee arthroplasty (1%–2%) [ 22 ]. Similar to previous studies, deep periprosthetic infection was found and treated in 14 (12%) of 121 patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Periprosthetic infection is a major postoperative complication of prosthesis. Tumor prosthesis has been shown to have a much higher postoperative infection rate (8%–15%) [ 10 , 19 , 21 ] compared with routine total joint replacements such as total hip arthroplasty and total knee arthroplasty (1%–2%) [ 22 ]. Similar to previous studies, deep periprosthetic infection was found and treated in 14 (12%) of 121 patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, deep periprosthetic infection was found and treated in 14 (12%) of 121 patients in our cohort. Treatment of deep periprosthetic infection has been reported as either a one-stage revision or two-stage revision, and two-stage revision has demonstrated a lower incidence of reinfection [ 10 , 19 , 23 , 24 , 25 , 26 ]. Our series has also shown that only five patients (36%) could be controlled by one-stage revision; the other patients required multiple or additional surgery such as two-stage revision and musculocutaneous flap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study group, revision surgeries were not performed. This was due to the fact that the study aimed to present the early treatment outcomes, while the number of complications increases with time that elapses since the surgery [12,14,20,21,22].…”
Section: Discussionmentioning
confidence: 99%